2012
DOI: 10.4161/epi.20584
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of active chromatin modifications in early mammalian embryos reveals uncoupling of H2A.Z acetylation and H3K36 trimethylation from embryonic genome activation

Abstract: (2012) Analysis of active chromatin modifications in early mammalian embryos reveals uncoupling of H2A.Z acetylation and H3K36 trimethylation from embryonic genome activation, Epigenetics,7:7,[747][748][749][750][751][752][753][754][755][756][757]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 60 publications
8
47
1
Order By: Relevance
“…One can speculate that the rise of H3K36me3 at 4-cell stage is a response to an extensive polymerase pause release that promotes EGA and that does not happen again until blastocyst. However, Bošković et al reported that, in mouse, H3K36me3 was only present in maternal chromatin immediately after fertilization and was absent in other stages of embryos, but was absent in all stages of bovine preimplantation embryos after fertilization [56]. These observations contrast with our results, possibly because of differences in the antibodies used.…”
Section: Discussioncontrasting
confidence: 99%
“…One can speculate that the rise of H3K36me3 at 4-cell stage is a response to an extensive polymerase pause release that promotes EGA and that does not happen again until blastocyst. However, Bošković et al reported that, in mouse, H3K36me3 was only present in maternal chromatin immediately after fertilization and was absent in other stages of embryos, but was absent in all stages of bovine preimplantation embryos after fertilization [56]. These observations contrast with our results, possibly because of differences in the antibodies used.…”
Section: Discussioncontrasting
confidence: 99%
“…These data confirm and extend the previous observation that H3K4me3 levels are first detectable at the MBT (Chen et al, 2013). Interestingly global H3K36me3 levels are also below the level of detection in the mouse embryo as it undergoes the first wave of zygotic genome activation (Boskovic et al, 2012). (Harrison et al, 2011).…”
Section: Early Transcription Does Not Require Marks Canonically Assocsupporting
confidence: 90%
“…For example, histone N-terminal tails are hyperacetylated in both paternal and maternal chromatins after fertilization [38]. In addition, asymmetric distribution of H3K36me3 and H3K79me2/3 are lost at the 1-cell stage, leading to global hypomethylation of these residues on both chromatins [39,40]. Furthermore, global replacement of histone variants, such as deposition of H3.3 to paternal chromatin as well as removal of H2A.Z and macroH2A from maternal chromatin [41,42], takes place soon after fertilization.…”
Section: Tet3-mediated 5mc Oxidation Is Dispensable For Zygotic Gene mentioning
confidence: 99%